Pengenalan Instalasi Programmable Logic Controller (Plc) Bagi Siswa Smk Muhammadiyah 3 Gresik - Pressa Perdana Surya; Rezki Setya Irsadi; Zainal Mustakim; Alviani Hesthi Permata N (ABIDUMASY, 2021)
Automation systems are vital for production departments in industry. One of the automation systems used in almost all industries is the programmable logic controller (PLC). The widespread use of PLC has long been applied as a standard curriculum in vocational schools (SMK). The widespread use of PLCs in the industrial world certainly increases job opportunities for vocational students who have expertise and skills in this field. In connection with this, the electrical engineering study program at the University of Muhammadiyah Gresik held PLC Zelio training for students of SMK Muhammadiyah 3 Gresik. This Zelio PLC training includes training in PLC wiring and installation, as well as the use of its PLC software. This training was held at the University of Muhammadiyah Gresik campus in the Automation and Instrumentation Laboratory. At the end of the training, SMK students were given a simple assignment according to the training material, namely assembling a Zelio PLC and making a simple program. From these assignments, all students are able to compose and make simple programs. Meanwhile, based on the questionnaire related to this training, all students also gave a score between 4 and 5, which means the training was quite good and satisfactory. It is hoped that with this training, students have the expertise and skills, especially in the field of PLC and are ready to enter the workforce after graduation.